ASUHAN KEPERAWATAN PADA Ny. F DENGAN TUBERCULOSIS PARU DENGAN MASALAH BERSIHAN JALAN NAFAS TIDAK EFEKTIF - Tiara Annisa; Efi Irwansyah Pane (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by Mycobacterium tuberculosis and attacks lung tissue. One of the common nursing problems found in patients with pulmonary TB is ineffective airway clearance, which is characterized by coughing up phlegm, shortness of breath, and additional breath sounds. Proper handling of this problem is very important to prevent further complications. This study was conducted to provide an overview of nursing care for clients with Pulmonary Tuberculosis respiratory system disorders who experience nursing problems of ineffective airway clearance. This case study used a nursing process approach that includes assessment, nursing diagnosis, planning, implementation, and evaluation. Data collection techniques were carried out through observation, interviews, physical examinations, and documentation studies. The results found that the main problem was ineffective airway clearance. Interventions carried out included the semi-Fowler position, effective coughing recommendations, administration of warm fluids, and sputum observation. The evaluation showed an improvement in symptoms in the form of reduced shortness of breath, easier sputum to expel, and improved breathing patterns. It was concluded that nursing care with a systematic approach can help improve respiratory function in patients with pulmonary TB with ineffective airway clearance problems.